PENGGUNAAN STRATEGI GUIDE NOTE TAKING BERBANTUAN VIDEO ANIMASI MOTION GRAPHIC PADA MATERI IPA DI SDN 12 PONTIANAK TIMUR - Ajie, Rizky Julianto; Setyaningrum, Vidya; Wahab, Wahab (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2023)
This research is motivated by the low learning outcomes of students and teachers who still use lecture and question-and-answer learning methods in science learning class 4 SDN 12 Pontianak Timur. The purpose of this study was to analyze the learning outcomes of students at the beginning, end, and how the effect of the guide note-taking strategy assisted by motion graphic animation video media. The method used is a quantitative experiment with the design